Managment of the mandibular dentigerous cyst plus rigid bone fixation, Presentation of a case - Navarrete Sarasty, Dario Xavier (2021)
The objective of this article is to present the management of a patient diagnosed with a mandibular dentigerous cyst. The present case deals with a 14-year-old male patient, without relevant antecedents who attended the SERODU dental clinic, a radiolucent shadow between the dental pieces 42, 44 and 45 was included in the computerized axial tomography with the part piece No. 43 included in the symphysis of the mandibular region, horizontal position of the dental piece, the crown towards the distal and its root towards the medial with complete formation. At the crown level, a well-defined radiolucent shadow can be observed with a radiopaque halo, compatible with a dentigerous cyst. Therefore, it was decided to carry  out the endodontic treatment in the dental pieces 43,44,45, subsequently the enucleation of the lesion, elimination of the dental piece, curettage and rigid bone fixation were performed, to avoid pathological complications of adjacent structures such as fracture mandibular due to the size of the lesion. A histopathological diagnosis of dentigerous cyst was obtained. At the thirty-day control, a radiopaque area compatible with bone regeneration was observed radiographically, with a radiolucent halo separating with the original basal bone. Enucleation and rigid bone fixation is an effective treatment technique to eliminate the lesion that turned out to be benign.